Penerapan Metode Kooperatif Tipe Jigsaw Untuk Meningkatkan Hasil Belajar IPA Pada Siswa Kelas V SD Negeri 1 Weda Kabupaten Halmahera Tengah - Wachyudi Eksan (Jurnal Ilmiah Wahana Pendidikan, 2022)
The sense of human digestion is an example of a learning resource that teachers can use for the benefit of student learning, especially in science subjects. the problem that occurred was that science subjects were not attractive to the fifth grade students at SD Negeri 1 Weda. Derived from the author's observations in class V of Elementary School 1 Weda it is known that the teacher does not involve students to be active in the learning process. based on what will happen in class V SD Negeri 1 Weda learning in the natural sciences subject matter of the sense of human digestion, the students' homogeneous values ​​are still below the KKM (65). so that there is a need for improvement in learning that aims to increase the results of learning science in the material of the human digestive system using the jigsaw cooperative method. This research means classroom action research (CAR) which was carried out in cycle II. originating as a result of data analysis and processing, the completeness score in cycle I means 13 students or 65% and the completeness score in cycle II is 19 students or 95%. This indicates that there is an increase in student learning outcomes of human digestive sensory material from cycle I to cycle II using the jigsaw cooperative method which can enhance student learning outcomes in science subjects.